Energy : production, conversion, storage, conservation, and coupling - Demirel, Yasar (London : Springer, 2012)
'Understanding the sustainable use of energy in various processes is an integral part of engineering and scientific studies, which rely on a sound knowledge of energy systems. Whilst many institutions now offer degrees in energy-related programs, a comprehensive textbook, which introduces and explains sustainable energy systems and can be used across engineering and scientific fields, has been lacking. Energy: Production, Conversion, Storage, Conservation, and Coupling provides the reader with a practical understanding of these five main topic areas of energy including 130 examples and over 600 practice problems.'--From publisher description.
Includes bibliographical references and index.
Keywords: Power resources; Power (Mechanics); Electrical engineering